PERAN GREENPEACE TERHADAP KONSERVASI GRAYWHALE DI KOREA SELATAN - Putri Nurkumala; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to determine about is the role of Greenpeace towards the conservation of graywhale in South korean. Greenpeace is non-governmental organization that handels the environment case like the hunt of graywhale, sea, energy, forest and chemical disposalIn this research, the writer uses methode of qualitative and quantitative research. This research describes international organization that has function to make campaign of revolution movement to solve the extinction threat of graywhaleIn this research, the problem is about the role of Greenpeace towards the conservation of graywhale which the hunt of whale especially graywhale whose population gets more crisis. Therefor,Greenpeace as environmental organization which it does campaign inits action and other activities to ask the society or government of South korean and global society for supporting conservation activity of graywhale, so this animal is not threatened extinct because of the graywhale hunt that is implemented by the society of South korean.Keyword:conservation,graywhale,greenpeace,role,southkorea,scientific whaling